Greenhouse Gases Mitigation by CO2 Reforming of Methane to Hydrogen-rich Syngas using Praseodymium Oxide Supported Cobalt Catalyst - Ayodele, Bamidele V.; Khan, Maksudur R.; Cheng, C. K. (Springer, 2016)
This study focuses on the potential of hydrogen rich syngas production by CO2 reforming of methane over Co/Pr2O3catalyst. The Co/Pr2O3catalyst was synthesized via wet-impregnation method and characterized for physicochemical properties by TGA, XRD, BET, H2-TPR, FESEM, EDX, and FTIR. The CO2reforming of methane over the as-synthesized catalyst was studied in a tubular stainless steel fixed-bed reactor at feed ratio ranged 0.1–1.0, temperature ranged 923–1023 K, and gas hourly space velocity (GHSV) of 30,000 h-1 under atmospheric pressure condition. The catalyst activity studies showed that the increase in the reaction temperature from 923 to 1023 K and feed ratio from 0.1 to 1.0 resulted in a corresponding increase in the reactant’s conversion and the product’s yields. At 1023 K and feed ratio of 1.0, the activity of the Co/Pr2O3 catalyst climaxed with CH4 and CO2 conversions of 41.49 and 42.36 %. Moreover, the catalyst activity at 1023 K and feed ratio of 1.0 resulted in the production of H2and CO yields of 40.7 and 40.90 %,respectively. The syngas produced was estimated to have H2:CO ratio of 0.995, making it suitable as chemical building blocks for the production of oxygenated fuel and other value-added chemicals. The used Co/Pr2O3 catalyst which was characterized by TPO, XRD, and SEM-EDX show some evidence of carbon formation and deposition on its surface.